Constructing a typology of male-on-male child molestation: a qualitative analysis of victims' narratives within the Boy Scouts of America. Issue 3 (2nd September 2021) - Shon, Leah; Tewksbury, Richard
ABSTRACT: This study examined details of behavioural sequences that constitute male-on-male child molestation within the Boy Scouts of America based on the narratives reported by child victims. Previous studies largely focused on convicted offenders when reconstructing the circumstances of child molestations. Also, sex crime literature did not consistently distinguish victim's gender and age when it comes to child victims and child molestation in an educational setting. Such loopholes have made the significances of the behavioural patterns in male-on-male child molestation unknown. This qualitative study analyses the verbal and behavioural patterns of male adult scoutmaster perpetrators against boy victims at the physical contact stage. Using a fishing metaphor, we identify unique behavioural sequences of scoutmaster perpetrators and explain the implications of such behaviours in male-on-male child molestation. Details of three unique behavioural patterns of scoutmaster perpetrators in male-on-male child molestation within the Boy Scouts of America are discussed.